Carbon Dioxide Capture From Internal Combustion Engine Exhaust Using Temperature Swing Adsorption - Sharma, Shivom; Maréchal, François (Frontiers in Energy Research, 2019)
Abstract: In order to reduce the CO2 emissions in the transportation sector, one can electrify the vehicle, switch to biofuel, or capture and store CO2 on board. In this study, integration of an on board CO2 capture and storage unit with an internal combustion engine has been proposed. The technology can be applied for various internal combustion or Stirling engines with targeted applications in the transportation sector. Truck transport for goods delivery is used as an example for on board CO2 capture and storage system design. The investigated system integrates a temperature swing adsorption system for CO2 capture with a turbo-compressor system to compress and liquefy the captured CO2 using the waste heat of the exhaust gases of the engine. Energy and exergy analyses of the proposed CO2 captured system are studied in details. The CO2 capture system for engine exhaust stream (car, truck, bus, ship or train) can capture 90% of the emitted CO2, without any energy penalty. This system can be integrated into overall mobility system (fuel-engine-CO2-fuel), where captured CO2 can be recycled as conventional liquid or gaseous fuels produced from renewable energy sources. Keywords: Carbon Dioxide Capture; Internal Combustion Engine; Exergy Analysis; Temperature Swing Adsorption; System Design and Integration; Heat Exchanger Network.